(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In the fast and furious world of Information Technology, one of the renowned phrase that has diminished all the vintage tools and boomed to a higher level with greater versatility of computing is cloud computing. It has created a stereotypical image that it could be more promising with multiple boons like flexibility, scalability, reliability and unsubstantial and limited operational costs. Though there are many valuable points to be considered in cloud computing, it has been noted that the latent cloud users are afraid of using this technology because of the unaddressed security reasons so that there is an exaggerated possibilities of hacking of information and loss of data. To overcome this scenario, we have taken an efficient approach in our research to facilitate the cloud users with proper asylum. In the stated article we examine the main covenant concerns present in this technology nowadays based on a skeleton for refuge subsists adopted from cloud service providers. Although there has been many solutions offered for this problem by many researchers, there are many flaws that has to be detected and eliminated out and has to be sorted out properly to enhance the users of cloud computing with exultation. Security issues linking to reliability, multitenancy, and group should be scrutinized extra fathomage for cloud to swamp over its security barricade and steps forward towards extensive agreement. The purpose of the paper is to offer a technique that enables Cloud Computing method to accomplish the efficiency of using the system assets and potency of the security examines without exchange between them.